(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The outbreak and the scale as a global pandemic of COVID-19 during this year has severely affected the education sector worldwide. The student population of the countries have been suffering much with primarily the lack of information about the modes and strategies of education conduct by the administrative bodies. In these trying times when most of the countries are adapting the internet-based teaching-learning strategy, the dire need of assessment of the methods implemented cannot be overlooked. In the educational pedagogy study, the analysis and indexing of the student’s satisfaction level should be of a prime concern of research. This paper primarily focuses on the study of various proposed methods till now to keep a record of the applied strategies and proposes the implementation of the Rasch analysis on the student satisfaction level. Moreover, the review of the works done till now is also carried out in order to investigate any scope of future work to provide a more efficient and effective method for the teaching-learning experience of the students in these trying times.